Pengaruh Alkitab terhadap Natal dan Implikasi Realitas Bisnis di Indonesia - Nole, Otniel Aurelius; Setyawan, Yusak Budi (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2024)
Christians believe that Christmas is a season to glorify the birth of Jesus Christ. However, the Christmas celebration is an issue intertwined with business realities. Researchers argue that the influence of the Bible intersects with Christmas. Nevertheless, some people use Christmas as a field to implement businesses that seek huge profits for personal satisfaction, thus creating social problems on the other side. This research aimed to analyze the Bible’s influence at Christmas and its implications for business realities in Indonesia. This research used a qualitative research method based on a literature review from a sociology of religion perspective. Researchers used scientific articles, proceedings, and books related to the research variables. This research showed that the Bible does influence Christmas. However, the Christmas atmosphere has implications for business realities that give rise to the spirit of capitalism. In this case, the social problems that occur are pressure and suffering. In essence, Christians reconstruct and rethink the nature and meaning of Jesus Christ’s birth in the Bible. Researchers provide scientific solutions, namely the actualization of celebrating Christmas humanistically in Indonesia.